The mediating role of dispositional resilience in the relationship between spirituality and life satisfaction of Filipino older adults - Gusilatar, Stephanie Joy Adriano; Calungsod, John Lloyd; Garcia, Akira; Santos, Beatriz; Ruiz, Wawie De Guzman (Frontiers in Psychology, 2025)
The study examined the relationship between spirituality and life satisfaction of Filipino older adults as mediated by dispositional resilience. Guided by the Selection, Optimization, and Compensation (SOC) model, the study employed a quantitative correlational design and a sample of 211 elderly Filipinos from Nueva Ecija, Philippines. Prior studies had established a nonlinear relationship of spirituality and life satisfaction, in contrast, this study attempted to provide a more definitive path between spirituality and life satisfaction. Moreover, previous researchers uncovered mediating effects of dispositional resilience with other concepts, whereas this study aimed to identify its role when mediating the aforementioned variables. Consequently, the findings revealed that spirituality and life satisfaction are positively correlated to dispositional resilience, the direct relationship of spirituality to life satisfaction was not significant. However, the effects of spirituality to life satisfaction can be amplified through the mediating effect of dispositional resilience. This indicates that dispositional resilience plays a significant role in understanding the influence of spirituality to the life satisfaction of Filipino older adults.